Agri‐Environment Scheme Design: Past Lessons and Future Suggestions. (5th June 2018) - Cullen, Paula; Dupraz, Pierre; Moran, James; Murphy, Pat; O'Flaherty, Ronan; O'Donoghue, Cathal; O'Shea, Robert; Ryan, Mary
Summary: This article summarises the views of a panel of experts from the areas of agricultural economics, ecology, agri‐environmental policy and agricultural extension who were bought together for a novel workshop on agri‐environment schemes conducted at the Agricultural Economics Society's 91 st Annual Conference. The panel discussed the past, present and future of European Union agri‐environment schemes with emphasis on the movement from top‐down action‐based schemes to participatory‐partnership results‐based schemes. Pierre Dupraz, an expert in economic evaluations of agri‐environment schemes, pointed out past issues of agri‐environment schemes including the conflicting objectives and the growing complexity. James Moran, an ecologist who has been involved in the design of results‐based schemes, identified the importance of designing schemes that are adaptable and incentivise farmers to improve. Ronan O'Flaherty, a senior policymaker involved in new scheme design in Ireland, shone a light on the policy behind agri‐environment schemes and the importance of stakeholder buy‐in. Pat Murphy, a knowledge transfer specialist involved in the implementation of agri‐environment schemes, discussed the importance that knowledge transfer must play in the future of agri‐environment schemes. Together the speakers identified the challenges faced in designing and implementing agri‐environment schemes that improve environmental outcomes whether they be action or results‐based. Abstract : This article summarises the views of a panel of experts from the areas of agricultural economics, ecology, agri‐environmental policy and agricultural extension who were bought together for a novel workshop on agri‐environment schemes conducted at the Agricultural Economics Society's 91 st Annual Conference. The panel discussed the past, present and future of European Union agri‐environment schemes with emphasis on the movement from top‐down action‐based schemes to participatory‐partnership results‐based schemes. Pierre Dupraz, an expert in economic evaluations of agri‐environment schemes, pointed out past issues of agri‐environment schemes including the conflicting objectives and the growing complexity.